Cadmian's choice - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Corean chronicles, 2006)
Millennia ago, a magical disaster caused the fall of a civilization, the end of a golden age. New civilizations emerged from the ancient destruction and chaos, knowing little of the past or the disaster. Corus today is a world of contending countries, humans, and supernatural creatures. It is a place of magical powers, and of a few people who are talented enough to use them. The time approaches for the transfer of the entire population of the old world, nearly bled dry of life force, to Corus. But neither Dainyl and the other Alectors, who face a reduced status, nor Mykel and the local humans, destined to become little more than cattle, are ready.